2021
DOI: 10.1177/00222194211006207
|View full text |Cite
|
Sign up to set email alerts
|

Language Difficulties in School-Age Children With Developmental Dyslexia

Abstract: Developmental dyslexia (DD) is a common reading disability, affecting 5% to 11% of children in North America. Children classified as having DD often have a history of early language delay (ELD) or language impairments. Nevertheless, studies have reported conflicting results as to the association between DD-ELD and the extent of current language difficulties in children with DD. To examine these relationships, we queried the parents of school-aged children with reading difficulties on their child’s early and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 65 publications
(144 reference statements)
2
14
0
1
Order By: Relevance
“…For the Toronto sample, we excluded children with known or suspected ASD, or with a first-degree relative with ASD, or other global/intellectual disabilities. Overlap between reading-and ASDassociated genes likely stemmed from shared genetic risk for neurodevelopmental disorders, particularly those contributing to language-related difficulties, as opposed to global delays [56,57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the Toronto sample, we excluded children with known or suspected ASD, or with a first-degree relative with ASD, or other global/intellectual disabilities. Overlap between reading-and ASDassociated genes likely stemmed from shared genetic risk for neurodevelopmental disorders, particularly those contributing to language-related difficulties, as opposed to global delays [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Toronto sample. The Toronto sample has previously been described and is part of an ongoing genetic study of RD-selected families recruited at the Hospital for Sick Children [53,56,66]. At the time of analysis, the sample consisted of children identified with reading difficulties (n = 453) and both their unaffected and affected siblings (n = 171).…”
Section: Methods Study Populations and Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…A menor fluidez fonológica menor comprensión verbal (H5). El estudio de Price et al (2021), enfocado a comprender las dificultades del LG, analizó una muestra de 323 niños con diagnóstico de DS; aplicaron pruebas psico-métricas, las puntuaciones de comprensión verbal, señalaron la existencia de deficiencias en el habla preexistentes antes de iniciar la etapa de escolarización, afectando posteriormente la adquisición de competencias académicas (fluidez y comprensión lectora).…”
Section: Discussionunclassified
“…In a longitudinal study, Snowling et al ( 34 ) demonstrated the influence of lower levels of linguistic competencies on the development of specific learning disorders. Moreover, linguistic deficits in already-diagnosed reading problems are observed retrospectively by parents more often than in average or good readers ( 35 ). Thus, asking parents about their children’s language performance and assessing it as an additional factor at school entry is anticipated to be a central component of a valid screening tool for written language skills.…”
Section: Introductionmentioning
confidence: 99%